FACTORS ASSOCIATED WITH ADOPTION LEVEL AND ADOPTION BEHAVIOUR OF FISH FARMERS ON BEST MANAGEMENT PRACTICES (BMPS) FOR FISH CULTURE IN ASSAM, INDIA - SAIKIA, PARAG; SARMA, DIPAK KUMAR; SAIKIA , RITUPARNA; SAHARIA, PABITRA KUMAR; KALITA, D.N.; DAFLARI, BHUPEN KUMAR; NATH, DHIREN KUMAR (Journal of the Inland Fisheries Society of India, 2026)
Better Management Practices (BMPs) for fish farming are a standardized set of farming practices to ensure the environmental and financial sustainability of fish farming systems. The adoption of BMPs of fish culture and the associated factors was studied different districts of Assam (Nagaon, Kamrup, Jorhat, Cachar and Sonitpur) each district located in different agro-climatic zones as part of the Assam Agribusiness and Rural Transformation Project (APART)- fishery, Assam. Using a three point Likert scale, respondents’ level of agreement with forty seven recommended technological practices in the implementation of proposed APART fish production technologies were assessed. The overall adoption rate was approximately 73.27%. Using factor analysis, all the partly adopted BMPs were categorized into seven thematic factors: optimised management and input supply, improved management practices, aquaculturemanagement practices, culture system practices, productivity and input management, routine maintenance and priority area before stocking. Although adopting the BMPs is voluntary, the practices crucial to the success of a crop were adopted by all the farmers, whereas those that involved significant cost were left out.